Město: (Pojem a kategorie) - Weber, Max (Lidé města, 2006)
In the edition “Archiv für Sozialwissenschaften und Sozialpolitik”, Volume 47, dated 1921, the famous Max Weber’s essay “The City“ that later became known to researchers under this title on urban problems, was published for the first time. This essay was also included under the same title as Chapter VIII in the comprehensive anthology “Wirtschaft und Gesellschaft” (Grundriß der Sozialökonomik, Section III), Tübingen 1922. The editor of the 4th issue, dated 1956, Johannes Winckelmann, reformulated the title as follows: “Illegitimate rule (Typology of Cities)”. This work is divided into 5 sections: Section 1: Notion and category of a city, Section 2: City of the Occident, Section 3: Feudal town in middle ages and antiquity, Section 4: Plebeian town, and Section 5: Roman and middle ages democracy. In the very first Czech translation we publish the first section, only.